Transcrestal Sinus Lift Procedure Approaching Atrophic Maxillary Ridge: A 60-Month Clinical and Radiological Follow-Up Evaluation - G. Lo Giudice; G. Iannello; A. Terranova; R. Lo Giudice; G. Pantaleo; M. Cicciù (Hindawi Limited, 2015)
Aim. The aim of this study was to assess the success and the survival rate of dental implants placed in augmented bone after sinus lifting procedures. Material and Methods. 31 patients were mainly enrolled for a residual upper jaw crest thickness of 3 mm. CBCT scans were performed before and after the augmentation technique and at the follow-up appointments, at 3, 6, 12, 24, and up to 60 months. The follow-up examination included cumulative survival rate of implants, peri-implant marginal bone loss, and the height of sinus floor augmentation. Results. This retrospective study on 31 patients and 45 implants later inserted in a less than 3 mm crest showed excellent survival rates (99.5%), one implant was lost before loading due to an acute infection after 24 days, and two implants did not osteointegrate and were removed after 3 months. The radiological evaluation showed an average bone loss of 0.25 mm (±0.78 mm) at the first follow-up appointment (3 months) up to 0.30 mm (±1.28 mm) after 60-month follow-up. Conclusion. In this study it was reported how even in less than 3 mm thick crest a transcrestal technique can predictably be used with a long-term clinical and radiological outcome, giving patients excellent stability of the grafted material and healthy clinical results.